(untitled) (Research, Society and Development, 2022)
The prevalence of intestinal parasites in the population is related to poor sanitation and poor hygienic habits. The present study aims to detect, both quantitatively and qualitatively, enteroparasitic agents in raw lettuce (Lactuca sativa) purchased in public markets in neighborhoods in the region of Recife - PE, using the HDIM as a socioeconomic indicator to make a comparison. We analyzed 12 samples of crisp lettuce (Lactuca sativa) collected in six different neighborhoods and used the 24-hour sedimentation method followed by centrifugation to search for intestinal parasites. A total of 324 enteroparasitic agents were detected and among them were: Giardia lamblia (28.4%), Strongyloides stercoralis (24.8%) and Entamoeba Coli (19%). All the markets analyzed presented more than one type of enteroparasite, but it was not possible to confirm whether there is a correlation between the enteroparasite findings and the socioeconomic index HDIM.